Targeting protein kinase C in an autoimmune diabetes mouse model - DiLisio, James E., author; Podell, Brendan K., advisor; Basaraba, Randall J., committee member; Lark, Daniel S., committee member (Colorado State University. Libraries, 2020)
Protein kinase C, a family of intracellular signal transducing proteins, are critical for a myriad of cellular actions with implications in both diabetes and its complications. The isoform PKCθ is enriched in T lymphocytes and functions to mediate signal transduction during T cell receptor stimulation. PKCθ has been shown to play a role in T cell mediated autoimmunity, whereby its activation increases autoimmune T cell function and suppresses that of regulatory T cells. We hypothesize that specific inhibition of PKCθ in autoimmune diabetes will enhance islet tolerance, increase regulatory T cell phenotypes, and delay the onset of overt diabetes in the NOD mouse model. A cell permeable, pseudo-substrate peptide inhibitor was shown to inhibit T cell receptor activation, in both in vitro T cell stimulations and ex vivo isolated T cells from treated mice. Pre-diabetic NOD mice treated daily with the peptide inhibitor for 4 weeks exhibited increased glucose tolerance at 15 weeks of age as well as increases in regulatory T cell phenotypes and reduced insulitis at 17 weeks of age in comparison to controls. Through long term diabetes onset studies, the peptide inhibitor slightly reduced the incident rate and delayed the onset of diabetes in a subset of animals. The moderate effects observed in preventing disease may be attributed to low efficacy or stability of the peptide inhibitor in vivo, which might be remedied by either genetic or pharmacological ablation of PKCθ activity. However, our data demonstrate the potential for targeting PKCθ in autoimmune diabetes as an immunotherapy to prevent or delay disease by increasing tolerance through the expansion of protective regulatory T cells.
Keywords: pkc theta; autoimmune diabetes; type 1 diabetes; regulatory t cells; T cells